Wireless networks : design and integration for LTE, EVDO, HSPA, and WiMAX - Smith, Clint; Collins, Daniel (New York : McGraw Hill, 2014)
Fully updated throughout to address current and emerging technologies, standards, and protocols, this book explains wireless system design, high-speed voice and data transmission, internetworking protocols, and 4G convergence. New chapters cover LTE, WiMAX, WiFi, and backhaul. You will learn how to successfully integrate LTE, WiMAX, UMTS, HSPA, CDMA2000/EVDO, and TD-SCDMA into existing cellular/PCS networks. Configure, manage, and optimize high-performance wireless networks with help from this thoroughly revised, practical guide
Previous edition: 2007
Includes bibliographical references and index
Keywords: Computer Communication Networks; Local area networks (Computer networks); Wide area networks (Computer networks); Wireless communication systems